Konservasi Lingkungan Melalui Penghijauan dalam Prespektif Hadis - Nailul Izzata Gufron; Romlah Abubakar Askar; Abdul Ghofur (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The increasingly complex issue of environmental degradation demands a holistic approach, including a religious perspective. This study explores environmental conservation through reforestation from the perspective of the hadiths of Prophet Muhammad (PBUH), focusing on the Islamic ecotheological values reflected in his sayings. This is a qualitative study using a library research method, collecting data from collections of hadith and relevant Islamic literature. The findings indicate that Islam, through the Prophet's hadiths, places great emphasis on environmental preservation, particularly through tree planting. The analyzed hadiths portray tree planting as a form of ongoing charity (ṣadaqah jāriyah), a social contribution, and a moral-spiritual responsibility of Muslims toward the Earth. Furthermore, reforestation is not merely seen as a physical act, but also as a form of worship rewarded by God. Planting trees is even encouraged during doomsday conditions, reflecting the profound ecological values within Islamic teachings. Thus, environmental conservation through reforestation in the hadith perspective embodies the values of tawḥīd (monotheism), khilāfah (stewardship), and amānah (trust) of humans as Earth’s caretakers. This study reaffirms that Islamic teachings are highly relevant in addressing today’s ecological crises.